2021
DOI: 10.1029/2020jb021154
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Scale Seismic Anisotropy Analysis in Metamorphic Rocks From the COSC‐1 Borehole in the Scandinavian Caledonides

Abstract: Metamorphic and deformed rocks in thrust zones show particularly high seismic anisotropy causing challenges for seismic imaging and interpretation. A good example is the Seve Nappe Complex in centralSweden, an old exhumed orogenic thrust zone that is characterized by a strong but incoherent seismic reflectivity and considerable seismic anisotropy. However, only little is known about their origin in relation to composition and structural influences on measurements at different seismic scales. Here, we present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 95 publications
(197 reference statements)
1
6
0
Order By: Relevance
“…However, Alkhalifah & Larner (1994) indicated that the use of Thomsen's parameters is permissible even for media with higher anisotropy. While the transverse isotropic symmetry is a valid assumption for the mica-rich units, much of the upper units (amphibolite and felsic gneiss) at the borehole may also be described by a lower symmetry system, such as orthorhombic symmetry (Kästner et al 2021). Despite these simplifications, we could observe a significant increase in the amplitudes and continuity of reflections.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, Alkhalifah & Larner (1994) indicated that the use of Thomsen's parameters is permissible even for media with higher anisotropy. While the transverse isotropic symmetry is a valid assumption for the mica-rich units, much of the upper units (amphibolite and felsic gneiss) at the borehole may also be described by a lower symmetry system, such as orthorhombic symmetry (Kästner et al 2021). Despite these simplifications, we could observe a significant increase in the amplitudes and continuity of reflections.…”
Section: Discussionmentioning
confidence: 74%
“…To test its effect on the reflection image, we therefore assumed a vertically transverse isotropic medium with values of ε and δ much lower than 1. According to Kästner et al (2021), the latter is justified for most of the upper parts of the COSC-1 borehole, whereas the deeper borehole parts show considerably higher values of anisotropy (Fig. 3).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The role of mica in seismic anisotropy has been relatively well studied because mica is recognized as a major contributor to observed seismic anisotropy in middle crustal settings owing to its high anisotropy and the common development of preferred shape and crystallographic orientation (e.g., Barruol & Mainprice, 1993; Christensen, 1965; Dempsey et al., 2011; Kästner et al., 2021; Lloyd et al., 2009; Shapiro et al., 2004; Ward et al., 2012). However, we are not aware of studies that have explored the relationship between mica content and seismic velocity contrast, so here we employ synthetic microstructures to explore this relationship and compare our results to published velocity data from natural rocks with varying mica content.…”
Section: Discussionmentioning
confidence: 99%
“…The microfracture closure pressure (Pc), above which velocities increase linearly, is dependent on rock type and shape of pores and microfractures (e.g., Walsh, 1965). For taking intrinsic seismic properties of the rocks and comparison with EBSD analysis of the SCSZ samples and the other 21 rocks (Ji et al., 2015; Kästner et al., 2021; Lloyd et al., 2009; Naus‐Thijssen, Goupee, Johnson, et al., 2011; Watling, 2017), we obtained the pressure derivative (d V /dP) and the velocity intercept V 0 at zero pressure by making and extrapolating a linear regression fit to the high‐pressure part of each velocity–pressure curve above Pc (e.g., Almqvist & Mainprice, 2017; Burlini & Fountain, 1993; Ji et al., 2007; Kästner et al., 2021; Kern et al., 2001; Khazanehdari et al., 2000). This relationship in the linear regime is described by V(P)=V0+(normaldV/normaldP)normalP $V(\mathrm{P})={V}_{0}+(\mathrm{d}V/\mathrm{dP})\mathrm{P}$.…”
Section: Discussionmentioning
confidence: 99%